2019
DOI: 10.1590/0104-6632.20190361s20170433
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid-Producing Yeasts in the Brazilian Biodiversity: Isolation, Identification and Cultivation in Agroindustrial Waste

Abstract: Different yeast strains from forests located in southern Brazil, with potential to produce carotenoids, were isolated. Three microorganisms were selected as potential carotenoid producers. Sporiodiobolus pararoseus, Rhodotorula mucilaginosa and Pichia fermentans were grown in Yeast Malt (YM) medium and the carotenoids produced identified as cryptoxanthin and β-carotene. In order to reduce production costs, agroindustrial residues were used in the formulation of medium A (parboiled rice water and crude glycerol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…From this period, the biomass had a slower growth, with oscillations of up to 168 h, reaching a value of 8.0. In the studies by Otero et al [33], with the Rhodotorula genus, a rapid consumption of reducing sugars was verified, 50% reduction in the first 24 hours of cultivation in an agro-industrial coproduct (parboiled rice water and sugarcane molasses). This consumption is due to conversion to biomass that doubled in the first few hours of cultivation.…”
Section: Confirmation Experimentsmentioning
confidence: 91%
“…From this period, the biomass had a slower growth, with oscillations of up to 168 h, reaching a value of 8.0. In the studies by Otero et al [33], with the Rhodotorula genus, a rapid consumption of reducing sugars was verified, 50% reduction in the first 24 hours of cultivation in an agro-industrial coproduct (parboiled rice water and sugarcane molasses). This consumption is due to conversion to biomass that doubled in the first few hours of cultivation.…”
Section: Confirmation Experimentsmentioning
confidence: 91%
“…Three yeast strains isolated in the Brazilian forests, belonging to the species Sporidiobolus pararoseus , Rh. mucilaginosa , and Pichia fermentans , were found to produce cryptoxanthin and β-carotene when they were cultivated in the media containing parboiled rice water and crude glycerol or parboiled rice water and sugar cane molasses [ 155 , 156 ].…”
Section: Biotechnologymentioning
confidence: 99%
“…These include enzymes, antibiotics, and biopigments that can be produced by submerged and/or solid fermentation of nutrientrich wastes [3][4][5]. Studies on the replacement of traditional culture media with agro-industrial wastes demonstrated increments of up to 50% pigment production by fungi [6]. Compared with fungal pigments, most bacterial pigments are still at the research and development stage; thus, it is necessary to intensify the research on bacterial pigment production to make them available on the market [7].…”
Section: Introductionmentioning
confidence: 99%